Persepsi Masyarakat Terhadap Kebijakan Subsidi Energi dan Implikasinya Terhadap Konsumsi Rumah Tangga - A, Arniya; N, Norpaizah; R, Rifayani; Pangestoeti, Wahjoe (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Energy subsidies are one of the fiscal policy instruments aimed at maintaining public purchasing power and national economic stability. However, in practice, energy subsidies are often criticized for being misdirected and placing a heavy burden on the State Budget. This study aims to examine public perceptions of energy subsidy policies and analyze their implications for household energy consumption. The research employed a descriptive qualitative approach, conducted in Tanjungpinang City, with data collected through literature reviews from relevant academic and policy sources. The findings indicate that most people support the existence of energy subsidies as they help reduce household expenditure burdens. However, such support is not always accompanied by a comprehensive understanding of the policy's goals and impacts, resulting in wasteful energy consumption patterns. Changes in subsidy policy significantly affect household spending, with low-income groups being the most affected. Moreover, positive public perception plays a crucial role in enhancing policy implementation effectiveness. Therefore, the government should develop effective public communication strategies and more targeted subsidy systems to foster sustainable energy consumption behavior.